Meiotic epigenetic factor PRDM9 impacts sperm quality of hybrid mice - Kusari, Fitore; Mihola, Ondrej; Schimenti, John C; Trachtulec, Zdenek (Reproduction, 2020)
Reduced fertility of male mouse hybrids relative to their parents, or hybrid sterility, is governed by the hybrid sterility 1 (Hst1) locus. Rescue experiments with transgenes carrying sequences within or near Hst1 manifested that Hst1 contains the gene encoding meiosis-specific histone methyltransferase PRDM9. The Prdm9 gene is responsible for partial meiotic arrest, testicular atrophy, and low sperm count in (C57BL/6J x PWD)F1 mouse hybrids. Here we report that these male hybrids suffer an additional reproductive disadvantage, decreased sperm quality, which is (i) further exacerbated by the introduction of long transgenes carrying sequences from Hst1 with incomplete Prdm9 into their genome and (ii) controlled by the Prdm9 dosage. These transgenic male hybrids displayed the features of severe oligoasthenoteratozoospermia (OAT), a human infertility syndrome characterized by a low number of spermatozoa with poor motility and morphological abnormalities. Analysis of spermiogenesis in these mice revealed acrosome detachment, aberrant elongation and condensation of the nucleus. As a result, the transgenic sperm had acrosome malformations, abnormal chromatin packaging, and fragmented DNA with elevated base oxidation, revealed by using multiple methods. Heterozygosity for one null Prdm9 allele improved meiotic progression and sperm quality of both non- and transgenic hybrids. Our results indicate that genomic analysis of OAT patients should include consideration of allelic variants in PRDM9, and our transgenic models can serve as tools to understand the diverse molecular processes that, when perturbed, can cause this disease.
Keywords: Mice, Transgenic; myši transgenní; Gene Expression Regulation; Infertility, Male; mužská infertilita; oligospermie; meióza; myši; Histone-Lysine N-Methyltransferase; Mice; Sperm Motility; motilita spermií; mužské pohlaví; zvířata; Meiosis; Mice, Inbred C57BL; Animals; Male; regulace genové exprese; Oligospermia; histonlysin-N-methyltransferasa; myši inbrední C57BL